Chemical composition of different oregano (origanum vulgare l.) essential oils: relevance for the activity against foodborne and spoilage bacteria - Amaral, Joana S. (2012)
Herbs and spices have been used for centuries in culinary for seasoning and flavouring purposes. More recently, there has been a growing interest regarding the use of some plants and its essential oils (EO) for their activity against foodborne pathogens and foodspoilage bacteria. Due to its potential in extending the self-life of foods and its better acceptability by consumers who demand more “natural” foods, the use of EO can be an interesting alternative to substitute, at least partially, synthetic preservatives.